Neutrophil but not Monocyte Activation Inhibits P-Selectin-Mediated Platelet Adhesion - Rinder, Henry M; Tracey, Jayne L; Rinder, Christine S; Leitenberg, David; Smith, Brian R (Thrombosis and Haemostasis, 1994)
Selectins are Ca2+-dependent glycoprotein receptors that mediate the adhesion of activated platelets or endothelial cells to unstimulated leukocytes. Using purified cell fractions, we examined activated neutrophil adhesion to P-selectin-expressing platelets and found that phorbol 12-myristate 13-acetate (PMA), platelet activating factor C16 (PAF), and n-formyl-met-leu-phe (fMLP) pretreatment of neutrophils inhibited activated platelet adhesion. Furthermore, PMA and PAF were capable of dissociating established resting neutrophil-activated platelet conjugates. Since L-selectin is downregulated after leukocyte activation and has been postulated as a ligand for P-selectin, we preincubated resting neutrophils with Dreg-2 and Dreg-56, blocking monoclonal antibodies (MoAb) to L-selectin; these MoAb failed to inhibit activated platelet adhesion. To more closely approximate in vivo conditions of leukocyte and platelet activation, we also employed a whole blood (WB) model of leukocyte-platelet adhesion. We found that simultaneous activation of both platelets and leukocytes by PMA caused an immediate rise in the % of P-selectin-positive platelets accompanied by a rapid increase in monocyte-platelet and neutrophil-platelet conjugates; however, the % of neutrophil-platelet conjugates subsequently declined over 30-60 min to baseline levels while monocyte-platelet adhesion remained elevated over 90 min. By contrast, selective platelet activation in WB by thrombin resulted in an increase in platelet P-selectin expression accompanied by a sustained (90 min) elevation in both monocyte- and neutrophil-platelet conjugates. This increase in leukocyte-platelet conjugates after thrombin was not inhibited by preincubation of WB with Dreg-2 or Dreg-56. We conclude that neutrophil activation decreases the expression of the ligand for platelet P-selectin within 30-60 min resulting in inhibition of neutrophil-platelet adhesion and dissociation of existing neutrophil-platelet conjugates. By contrast, monocyte activation over 90 min does not affect monocyte adhesion to activated platelets in whole blood.